2020
DOI: 10.1111/zph.12713
|View full text |Cite
|
Sign up to set email alerts
|

Porcine rotavirus C strains carrying human‐like NSP4 and NSP5

Abstract: Background Rotavirus C (RVC) is an enteric pathogen that affects humans and animals around the world. Methods In this study, we characterized the genetic diversity of RVC strains detected in asymptomatic Brazilian pigs by sequencing the NSP4, NSP5 and VP6 genes. Results The results of reverse transcription polymerase chain reaction showed that 53 of 579 samples (9.2%) contained RVC. Positive samples were genotyped by sequencing gene segments NSP4, and NSP5. Most of the RCV strains encountered were classified i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 23 publications
0
5
0
Order By: Relevance
“…Reassortment of rotaviruses may lead to the development of zoonotic potential in animal rotaviruses, causing human diseases [23–26]. Despite some reports of porcine RVC strains that carry human-like segments [2], we have not seen very closely related human and animal RVC strains at the whole-genome level. In this study, however, we have observed some segments with very high identity between human and porcine strains.…”
Section: Discussionmentioning
confidence: 90%
See 3 more Smart Citations
“…Reassortment of rotaviruses may lead to the development of zoonotic potential in animal rotaviruses, causing human diseases [23–26]. Despite some reports of porcine RVC strains that carry human-like segments [2], we have not seen very closely related human and animal RVC strains at the whole-genome level. In this study, however, we have observed some segments with very high identity between human and porcine strains.…”
Section: Discussionmentioning
confidence: 90%
“…We also found one strain that has two different N-segments, N1 and N9, but all other segments appear to be unique, single segments. Reassortment is a common way of generating variations in viruses with a segmented genome [2,12,21,22]. Yet, we have not seen reports on a strain that has more than one segment for a given gene.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…Rotavirus C (RVC) is a significant cause of diarrhea globally, affecting individuals of all age groups [ 13 , 14 , 15 ]. Its first report dates back to 1980 when it was identified in pigs in the United States [ 16 ], and subsequent studies have identified it in humans, dairy cattle, ferrets, and dogs [ 17 , 18 , 19 , 20 , 21 ]. RVC infections in pigs have been reported worldwide, often associated with epidemics of diarrhea [ 22 , 23 , 24 , 25 ].…”
Section: Introductionmentioning
confidence: 99%